Analisis Konsep Diri Pada Siswi SMKN 1 Sragen - Bowo Wijianto (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research aims to explore the self-concept of female students at SMKN 1 Sragen using a qualitative approach through interview methods. The research sample consisted of seven female students from the total population of female students at SMKN 1 Sragen. The analysis results indicate that the self-concept of female students at SMKN 1 Sragen is categorized as positive across physiological, psychological, psycho-social, and psycho-spiritual aspects, exhibiting diversity in self-concept and influencing factors, categorized into internal and external factors. The findings of this research offer profound insights into the development of adolescent self-concept, along with its potential implications for personal development and social interactions.